In arthritis the Doppler based degree of hypervascularisation shows a positive correlation with synovial leukocyte count and distinguishes joints with leukocytes greater and less than 5/nL - Löffler, Christian; Sattler, Horst; Peters, Lena; Tuleweit, Anika; Löffler, Uta; Wadsack, Daniel; Uppenkamp, Michael; Bergner, Raoul (Joint bone spine, 2016)
Objectives - Power Doppler ultrasound is used to assess joint vascularity in acute arthritis. PDUS signals have been correlated with synovial histology and bone deterioration. Little is known about the correlation between power Doppler signals and synovial white blood count. In our study, we analyzed power Doppler signals in inflammatory joint diseases including gout, calcium pyrophosphate deposition disease, rheumatoid arthritis, spondyloarthritis and others and correlated power Doppler signals with synovial white blood count and with serologic markers of inflammation. - Methods - We retrospectively evaluated 194 patients with arthritis. All patients underwent joint sonography, power Doppler ultrasound, synovial fluid analysis and blood examination of C-reactive protein and erythrocyte sedimentation rate. Correlation analyses (Spearman and Pearson), Chi2 test, t-tests, a unifactorial ANOVA and regression analyses were applied. - Results and conclusions - Hypervascularisation in power Doppler was most prominent in gout and calcium pyrophosphate deposition disease. Spondyloarthritis and non-inflammatory joint diseases presented with low degrees of hypervascularisation. Mean synovial white blood count did not differ significantly between crystal-related arthritides, rheumatoid arthritis, spondyloarthritis or other inflammatory joint diseases. There was a positive but weak correlation between power Doppler signals and synovial white blood count (P<0.001, rs=0.283), erythrocyte sedimentation rate (P<0.001, rs=0.387) and C-reactive protein (P<0.001, rs=0.373) over all diagnoses. This was especially relevant in rheumatoid arthritis (P<0.01, rs=0.479). Power Doppler degrees 0 and 1 were able to predict synovial leukocytes<5/nL, degrees 2 and 3 predict leukocytes⿥5/nL (P<0.001).